Concept art - minimal - arte povera - land art : Sammlung Marzona. - Franz, Erich; Lippert, Werner; Weisner, Ulrich; Kunsthalle Bielefeld (Stuttgart : Edition Cantz, 1990)
Acconci, Vito ; Andre, Carl ; Anselmo, Giovanni ; Baldessari, John ; Barry, Robert ; Becher, Bernd & Hilla ; Bendgens, Rolf ; Bergmann-Michel, Ella ; Bochner, Mel ; Brancusi, Constantin ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Charlton, Alan ; Darboven, Hanne ; Dibbets, Jan ; Duchamp, Marcel ; Riverhead (New York) ; Fulton, Hamish ; Gilbert & George ; Graham, Dan ; Huebler, Douglas ; Judd, Donald ; Kawara, On ; Kosuth, Joseph ; Kounellis, Jannis ; Kuehn, Gary ; LeWitt, Sol ; Lissitzky, El ; Lohaus, Bernd ; Long, Richard ; Mangold, Robert ; Manzoni, Piero ; Marden, Brice ; Matta-Clark, Gordon ; McLean, Bruce ; Merz, Mario ; Meyer, Hannes ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Morris, Robert ; Nauman, Bruce ; Oppenheim, Dennis ; Palermo, Blinky ; Panamarenko ; Penone, Giuseppe ; Picabia, Francis ; Poons, Larry ; Richter, Gerhard ; Rodchenko, Alexander ; Rückriem, Ulrich ; Ruscha, Ed ; Ruthenbeck, Reiner ; Sandback, Fred ; Serra, Richard ; Smithson, Robert ; Tuttle, Richard ; Le Va, Barry ; Weiner, Lawrence
biog. p. 238-262
glossarium p. 263-265 (met verklaring van volgende begrippen : Anti-Form, Arte povera, Behaviour art, Body art, Concept Art, Fotografie, Land Art, Materialkunst, Minimal art, Monochromie, Prozesskunst, Ready-made, Textbild)
Duits
Concept art - minimal - arte povera - land art : Sammlung Marzona, Kunsthalle Bielefeld, 18. Februar - 8. April 1990
boek